2003
DOI: 10.1128/aem.69.9.5306-5318.2003
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics of the Nomenspecies Enterobacter cloacae

Abstract: The genetic heterogeneity of the nomenspecies Enterobacter cloacae is well known. Enterobacter asburiae, Enterobacter cancerogenus, Enterobacter dissolvens, Enterobacter hormaechei, Enterobacter kobei, and Enterobacter nimipressuralis are closely related to it and are subsumed in the so-called E. cloacae complex. DNA-DNA hybridization studies performed previously identified at least five DNA-relatedness groups of this complex. In order to analyze the genetic structure and the phylogenetic relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
280
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(288 citation statements)
references
References 47 publications
5
280
0
3
Order By: Relevance
“…Other targets for use for the molecular identification of isolates within the Enterobacter genus have been described, such as the oriC locus (23), gyrB (6), rpoB (8,21), and hsp60 (8). Sequence analysis of a fragment of the hsp60 gene showed that the E. cloacae nomenspecies could be divided into 12 genetic clusters (clusters I to XII) and one sequence crowd (sequence crowd xiii).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Other targets for use for the molecular identification of isolates within the Enterobacter genus have been described, such as the oriC locus (23), gyrB (6), rpoB (8,21), and hsp60 (8). Sequence analysis of a fragment of the hsp60 gene showed that the E. cloacae nomenspecies could be divided into 12 genetic clusters (clusters I to XII) and one sequence crowd (sequence crowd xiii).…”
mentioning
confidence: 99%
“…steigerwallti (cluster VIII) (10). Species names were not attributed to clusters III, IV, and IX and to sequence crowd xiii, although at least cluster III is of significant clinical importance (8,26).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…16S rRNA gene sequencing was performed using primers 8F and 1541R (Table 1) (Zhou et al, 1995) and the results were analysed using the EzTaxon server (Chun et al, 2007) and MEGA software (http://www.megasoftware.net). The primers for PCR and sequencing of the hsp60 gene were Hsp60 For and Hsp60 Rev (Table 1; Hoffmann & Roggenkamp, 2003). The DNA-DNA relatedness between strain YMC/KN/03/21 and the type strains of E. hormaechei CCUG 27126 T and E. asburiae CCUG 25714 T were evaluated using DNA-DNA hybridization.…”
Section: Methodsmentioning
confidence: 99%